The Functionalized Single-Walled Carbon Nanotubes Gas Sensor With Pd Nanoparticles for Hydrogen Detection in the High-Voltage Transformers - Tang, Sirui; Chen, Weigen; Zhang, He; Song, Zihao; Li, Yanqiong; Wang, Yu (Frontiers in Chemistry, 2020)
Single-walled carbon nanotubes (SWCNTs) have been wildly discussed and applied as novel gas sensing nanomaterials. Hydrogen is one of the remarkable fault characteristic gases in the high-voltage oil-paper insulated transformers. In this paper, 3.07 wt% Pd nanoparticles (NPs) were used to decorate SWCNTs. The unloaded, the carboxylated, and the Pd-doped SWCNTs were fabricated into three planar gas sensors, and their gas sensing properties to hydrogen were studied. Gas sensing mechanism was analyzed. Results shows that the optimal operating temperature of Pd-doped SWCNTs-based gas sensor is 125 ℃ lower than that of the unloaded SWCNTs-based gas sensor, and it shows the highest gas sensing response value. This is attributed to the decreasing of work function of Pd, which reducing the hole carries in the nanotubes.